The role of tumour microenvironment in gastric cancer angiogenesis - Brzozowa, Marlena; Michalski, Marek; Harabin-Słowińska, Marzena; Wojnicz, Romuald (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Gastric cancer is one of the most common cancers in the world. More than 95% of gastric cancers are adenocarcinomas originating from the glandular epithelium of the stomach lining. Unfortunately, a large number of patients are diagnosed when the tumour is at unresectable stage. Therefore, it is very important to understand the mechanisms involved in gastric cancer pathogenesis. One of them is angiogenesis, which means the formation of new blood vessels from pre-existing vasculature. This process is dependent on interactions between the tumour and surrounding stromal cells which create the tumour microenvironment. Moreover, both tumour and stromal cells release a wide array of angiogenic factors that have an influence on endothelial cell recruitment and thus affect the process of angiogenesis. In this paper we discuss the role of tumour microenvironment in gastric cancer angiogenesis.